ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2018-2020 - Angie Nathania; Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims to obtain empirical evidence on the impact of company value, financial risk, company age, and managerial ownership on income smoothing in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study used purposive sampling methods in sampling and obtained as many as 44 manufacturing companies as the final sample to be used. The data that has been collected is then processed using Eviews version 12 software. The results show that the variables of financial risk, company age, and managerial ownership have no effect on income smoothing. Meanwhile, company value variable has a significant negative effect on income smoothing.